2023
DOI: 10.3389/fcvm.2023.1005408
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin suppresses mitochondrial reactive oxygen species generation and mitigates the inducibility of atrial fibrillation in diabetic rats

Abstract: IntroductionRecent studies have demonstrated that sodium-glucose co-transporter-2 inhibitors (SGLT2-i) reduce the risk of atrial fibrillation (AF) in patients with diabetes mellitus (DM), in which oxidative stress due to increased reactive oxygen species (ROS) contributes to the pathogenesis of AF. We aimed to further investigate this, and examine whether the SGLT2-i empagliflozin suppresses mitochondrial-ROS generation and mitigates fibrosis.MethodsA high-fat diet and low-dose streptozotocin treatment were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 63 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…The results demonstrated that the pro-fusion proteins MFN1/2 and OPA1 were upregulated, and the pro-fission proteins DRP1 and FIS1 were downregulated after SGLT2i treatment ( 35 , 42 , 47 ). According to Koizumi et al, Empagliflozin brought the altered atrial protein expression associated with fission and fusion of mitochondria back to levels comparable to those observed in the control group ( 139 ). Additionally, 6 studies showed that SGLT2i increased the mitochondria number ( 34 ), length ( 35 ), pleomorphism ( 30 , 35 ), mean area ( 34 , 39 ) and MMP ( 42 , 47 ) while alleviating mitochondria irregular swelling, fractured cristae and fuzziness ( 35 ), implying an improvement in mitochondria structure.…”
Section: Discussionmentioning
confidence: 92%
“…The results demonstrated that the pro-fusion proteins MFN1/2 and OPA1 were upregulated, and the pro-fission proteins DRP1 and FIS1 were downregulated after SGLT2i treatment ( 35 , 42 , 47 ). According to Koizumi et al, Empagliflozin brought the altered atrial protein expression associated with fission and fusion of mitochondria back to levels comparable to those observed in the control group ( 139 ). Additionally, 6 studies showed that SGLT2i increased the mitochondria number ( 34 ), length ( 35 ), pleomorphism ( 30 , 35 ), mean area ( 34 , 39 ) and MMP ( 42 , 47 ) while alleviating mitochondria irregular swelling, fractured cristae and fuzziness ( 35 ), implying an improvement in mitochondria structure.…”
Section: Discussionmentioning
confidence: 92%
“…A recent analysis of the DECLARE-TIMI 58 study showed a 19% reduction in the incidence of AF in patients with diabetes, regardless of pre-existing AF or HF. Effective AF prevention can transform this approach into HF treatment [ 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…NOX has multiple isoforms that can influence various processes and contribute to chronic diseases, such as hypertension, hyperlipidemia, and HF [40]. Cardiovascular-related isoforms, NOX2 and NOX4, inhibit atrial remodeling and reduce inflammation associated with AF [40,41]. NOX activity is exacerbated in fibrillating atria, especially in the presence of systemic hormones such as Ang II and aldosterone [39].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…It has been shown that empagliflozin reduces reactive oxygen species and improves mitochondrial function ( 25 ). In our study, we found that empagliflozin reduces NOS2 expression, suggesting that empagliflozin reduces the induction of reactive nitrogen species, thereby reducing the mitochondrial oxidative stress ( Fig.…”
Section: Resultsmentioning
confidence: 99%